NUTRIENT RECOMMENDATIONS AND DIETARY GUIDELINES FOR PRAGNENT WOMEN - Uktamovich, Kadyrov Oybek; Gafurovna, Ashurova Nigora (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
At present, maternal and child health and upbringing of harmoniously developed generation have been identified as priorities of state policy in our country. Proper nutrition of children from infancy not only improves their physical health, but also reduces the risk of contracting infectious diseases and contributes to the further development of their social and psychological condition.